The unspeaking subaltern: Female domestic workers in Dhaka - Hasan, Md. Mahmudul (2019)
Although Bangladesh is one of the largest suppliers of interstate female domestic workers, most Bangladeshi female domestic helps work in urban and rural areas within the country. Dhaka, the capital and main city, has the highest concentration of female domestic service workers in the country. Compared to those Bangladeshi women who dare and manage to embark on foreign shores in search of economic opportunities, those who remain in the country and work as domestic workers come from more vulnerable and lower social strata, and from more impoverished families of mainly rural and slum backgrounds. Again, compared to those who work as domestic workers in rural areas, their counterparts in urban settings have more social disadvantages and are more likely to be subject to domestic violence and other forms of injustice. They live in, and do chores within, the four walls of the home and hence have little opportunity to socialise beyond the immediate confines of the house or to share with others their lived experiences and the treatment they receive from employing family members. Their silences, exclusions and relative invisibility make them perhaps the worst unspeaking subaltern. Often there are media reports on the oppression and exploitation of Bangladeshi domestic workers overseas, especially in the Gulf region. However, the stories of Dhaka’s female domestic helps are largely untold and unheard of. They are unlettered, unaware of the world beyond the domestic orbit and, when subjected to injustice, unable to challenge their disproportionately dominant employers. Sporadic reports that appear in the local media tell us very little about the full extent of their ground-level, quotidian experiences. Hence, Gayatri Spivak’s justly famous argument about the inability of the subaltern to speak or to have a voice is highly pertinent to the plight of Dhaka’s female domestic workers. Reflecting on their live-in and work experiences as household employees and as members of the secondary labour force, this research will contribute new perspectives on Spivak’s notion of the forcibly muted subaltern in relation to the plight of female domestic workers in Dhaka whose subalternity is perhaps more insidiously inhuman. Based on the backgrounds, and taking into account the enormity of the plight, of the female domestic helps in Dhaka, I will describe their experiences, explore their social origins, shed light on their relationships with the members of the employing family and discuss factors that exacerbate their vulnerability and restrict their capability to assert their rights.